Mr. Antonio Belaunde Moreyra: Personal and intellectual resemblance - Flores Quelopana, Gustavo (Mercurio Peruano, 2016)
This is not a panegyric nor ditirambo, but a personal and intellectual portrayal of a teacher in life and thought. The polyhedral genius made of strong Peruvianism and sincere and transcendent Christian faith shines through in the life and work of Don Antonio Belaunde Moreyra. Gifted with the depth of the philosopher, the intuition of the poet, the filigree of the writer and the fascination of the artist, he knew how to recover the alliance lost in the modern world between reason and heart.